The Role of Job Satisfaction in Mediating the Quality of Work Life Effect on Employee Performance - Rahayu Puji Suci; Nasharuddin Mas; Mochammad Risky (Universitas Hayam Wuruk Perbanas, 2022)
This study aims to obtain empirical evidence regarding the role of quality of work life (QWL) in increasing job satisfaction and employee performance, including the ability of job satisfaction to mediate the effect of QWL on employee performance. This study uses a quantitative approach and the method used to analyze data is SEM-PLS. Data are obtained through questionnaires which are distributed to 45 employees of the Regional Development Planning, Research and Development Agency of Batu City. The results show that high quality of work life has an effect on increasing job satisfaction and employee performance. High job satisfaction has an effect on increasing employee performance. In addition, job satisfaction mediates the effect of quality of work life on employee performance, even though the mediating role is partial. The implication of the findings of this research is the importance of the leadership of the Regional Development Planning, Research and Development Agency of Batu City in balancing the interests of the organization and the personal lives of its employees to increase the level of employee satisfaction, so that the performance of employees and the organization is getting better.